Pharmacogenomic Studies of Antiviral Drug Favipiravir - Victoria V. Shumyantseva; Tatiana V. Bulko; Alexey A. Chistov; Ekaterina F. Kolesanova; Lyubov E. Agafonova (MDPI AG, 2024)
In this work, we conducted a study of the interaction between DNA and favipiravir (FAV). This chemotherapeutic compound is an antiviral drug for the treatment of COVID-19 and other infections caused by RNA viruses. This paper examines the electroanalytical characteristics of FAV. The determined concentrations correspond to therapeutically significant ones in the range of 50-500 µM (R2 = 0.943). We have shown that FAV can be electro-oxidized around the potential of +0.96 V ÷ +0.98 V (vs. Ag/AgCl). A mechanism for electrochemical oxidation of FAV was proposed. The effect of the drug on DNA was recorded as changes in the intensity of electrochemical oxidation of heterocyclic nucleobases (guanine, adenine and thymine) using screen-printed graphite electrodes modified with single-walled carbon nanotubes and titanium oxide nanoparticles. In this work, the binding constants (Kb) of FAV/dsDNA complexes for guanine, adenine and thymine were calculated. The values of the DNA-mediated electrochemical decline coefficient were calculated as the ratio of the intensity of signals for the electrochemical oxidation of guanine, adenine and thymine in the presence of FAV to the intensity of signals for the electro-oxidation of these bases without drug (S, %). Based on the analysis of electrochemical parameters, values of binding constants and spectral data, intercalation was proposed as the principal mechanism of the antiviral drug FAV interaction with DNA. The interaction with calf thymus DNA also confirmed the intercalation mechanism. However, an additional mode of interaction, such as a damage effect together with electrostatic interactions, was revealed in a prolonged exposure of DNA to FAV.